The Effect of Emotional Intelligence and Leadership Skills on Organizational Commitment: A Case Study of Civil Servants - Aqsa Batool; Iram Batool; Aasma Aziz (Journal of Management Practices, Humanities and Social Sciences, 2024)
Organizational commitment is a crucial factor in the effectiveness and efficiency of civil servants, who often face unique challenges such as bureaucratic constraints and public scrutiny. Emotional intelligence and leadership skills foster organizational commitment among civil servants. So, the present study examined the effect of emotional intelligence and leadership skills on organizational commitment among civil servants. A cross-sectional study collected data from 302 civil servants of different districts of Punjab using convenience sampling. The Leadership Skills Questionnaire, Emotional Intelligence Scale, and Organizational Commitment Questionnaire were the measures to collect data from the participants. Statistical analysis was performed using SPSS 27. Correlational analysis revealed a positive and significant correlation among emotional intelligence, leadership skills, and organizational commitment. Multiple Regression analysis found that emotional intelligence and leadership skills have a significant positive effect on organizational commitment among civil servants. The civil servants who have more than five years’ experience depicted more organizational commitment, higher level of emotional intelligence and leadership skills than those who have less than five years’ experience. The findings suggested that fostering emotional intelligence and leadership skills among civil servants enhance organizational commitment leading to quality service delivery and effective job performance.